Analyses of partial diallel among brazilian and introduced potato cultivars - Henrique Pereira Barbosa, Márcio; Augusto Brasil Pereira Pinto, César (Pesquisa Agropecuaria Brasileira, 1998)
With the objective of evaluating the genetic potential and combining ability, seven introduced potato (Solanum tuberosum L.) cultivars were crossed by partial diallel scheme, with six national potato cultivars. The trials were conducted in Madre de Deus and Lavras, both in Minas Gerais State, Brazil, employing randomized complete block and augmented block design, respectively. The 57 treatments tested in Madre de Deus consisted of 13 parents, 42 clonal families and two checks, cultivars Achat and Baraka. In Lavras, 817 experimental clones were evaluated along with 13 parents and two common treatments, Achat and Baraka. General combining ability (GCA) was the principal component of variation among families for total and marketable tuber yield per plant, mean of tuber number per plant and specific gravity. For the other traits the contributions of GCA and specific combining abilities (SCA) were similar. Cultivars Baronesa, Mantiqueira and Monalisa had better stability of GCA for yield characters in both places and the families Baronesa x Monalisa and Mantiqueira x Atlantic had better performance for yield potential and good association of alleles as indicated by high values of SCA.
Keywords: combining ability; selection of clones